2019
DOI: 10.1177/1368430218813442
|View full text |Cite
|
Sign up to set email alerts
|

A social identity perspective on the social-class achievement gap: Academic and social adjustment in the transition to university

Abstract: First-generation students show lower academic performance at university compared to continuing-generation students. Previous research established the value in taking a social identity perspective on this social-class achievement gap, and showed that the gap can partly be explained by lower compatibility between social background and university identities that first- compared to continuing-generation students experience. The present paper aimed to increase insight into the processes through which this low ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Social identity threat and/or identity incompatibility have been found to reduce the performance of Black and Latino students in U.S. schools and colleges (Chu & Brown, 2017;Gonzales, Blanton, & Williams, 2002;Steele & Aronson, 1995); students and young children of lower social class in the United States (Désert, Préaux, & Jund, 2009;B. Spencer & Castano, 2007), France (Croizet & Claire, 1998), and Belgium (Veldman, Meeussen, & van Laar, 2019); children of immigrants in Belgium (Baysu, Celeste, Brown, Verschueren, & Phalet, 2016); women and girls in stereotypically masculine subjects such as maths and science (Ambady, Shih, Kim, & Pittinsky, 2001;Picho, Rodriguez, & Finnie, 2013;S. J. Spencer, Steele, & Quinn, 1999); and boys in general performance and in stereotypically feminine subjects such as reading, English, and languages (Hartley & Sutton, 2013;Pansu et al, 2016).…”
Section: Psychological Barriers Contribute To Educational Inequalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Social identity threat and/or identity incompatibility have been found to reduce the performance of Black and Latino students in U.S. schools and colleges (Chu & Brown, 2017;Gonzales, Blanton, & Williams, 2002;Steele & Aronson, 1995); students and young children of lower social class in the United States (Désert, Préaux, & Jund, 2009;B. Spencer & Castano, 2007), France (Croizet & Claire, 1998), and Belgium (Veldman, Meeussen, & van Laar, 2019); children of immigrants in Belgium (Baysu, Celeste, Brown, Verschueren, & Phalet, 2016); women and girls in stereotypically masculine subjects such as maths and science (Ambady, Shih, Kim, & Pittinsky, 2001;Picho, Rodriguez, & Finnie, 2013;S. J. Spencer, Steele, & Quinn, 1999); and boys in general performance and in stereotypically feminine subjects such as reading, English, and languages (Hartley & Sutton, 2013;Pansu et al, 2016).…”
Section: Psychological Barriers Contribute To Educational Inequalitiesmentioning
confidence: 99%
“…Although social identity threat and identity incompatibility have a range of consequences on educational outcomes, the most well‐documented is on academic performance. Social identity threat and/or identity incompatibility have been found to reduce the performance of Black and Latino students in U.S. schools and colleges (Chu & Brown, 2017; Gonzales, Blanton, & Williams, 2002; Steele & Aronson, 1995); students and young children of lower social class in the United States (Désert, Préaux, & Jund, 2009; B. Spencer & Castano, 2007), France (Croizet & Claire, 1998), and Belgium (Veldman, Meeussen, & van Laar, 2019); children of immigrants in Belgium (Baysu, Celeste, Brown, Verschueren, & Phalet, 2016); women and girls in stereotypically masculine subjects such as maths and science (Ambady, Shih, Kim, & Pittinsky, 2001; Picho, Rodriguez, & Finnie, 2013; S. J. Spencer, Steele, & Quinn, 1999); and boys in general performance and in stereotypically feminine subjects such as reading, English, and languages (Hartley & Sutton, 2013; Pansu et al., 2016). Indeed, estimates based on effect sizes derived from two meta‐analyses incorporating data from nearly 19,000 individuals suggests that threat accounts for 17–28% of the White–Black attainment gap on SATs, 23–39% of the White‐Latino SAT attainment gap, and 57–94% of the gender gap on SAT mathematics in the United States (Walton & Spencer, 2009; Walton et al., 2013).…”
Section: Psychological Barriers Contribute To Educational Inequalitiesmentioning
confidence: 99%
“…Other research has also shown that there can be a mismatch between qualities, values, or norms that tend to be associated with members of traditionally underrepresented groups and the settings they are entering and that this is subtly signaled in the context (Stephens et al, 2012a,b, 2014; Schmader and Sedikides, 2018; Veldman et al, 2019). For example, Gaucher et al (2011) showed that this may occur for women through job descriptions that use more masculine-themed words (e.g., emphasizing dominance, competitiveness).…”
Section: Potential Triggers Of Threat In the Workplacementioning
confidence: 99%
“…Another factor that impacts FGCS’ college retention and completion involves college choice, which is generally based on convenience of location and commuting (Garza & Fullerton, 2018) rather than institutional selection (Davies & Guppy, 1997), especially for those who must live at home due to lack of finances. Moreover, the type of institution attended (i.e., 2-year, 4-year, public, private, minority-serving, non-profit, or for-profit) can impact challenges on retention (Pascarella et al, 2003), which are grounded in students’ perceptions of fit within the institution (Gloria et al, 2005; Lubrano, 2003; Palardy, 2013), readiness for college experience (DeAngelo & Franke, 2016), structural and social integration issues (Billson & Terry, 1982; Veldman et al, 2019), sense of belonging (Morrow & Ackermann, 2012; O’Keeffe, 2013), cultural displacement (Próspero et al, 2012), and other formidable barriers (Engle & Tinto, 2008; Pascarella & Chapman, 1983; Pratt et al, 2019). These factors all reinforce how classist and elitist norms insidiously play a part in excluding lower SES students from opportunities to educationally advance.…”
Section: Literature Reviewmentioning
confidence: 99%